Financial markets and international risk sharing in emerging market economics - Martin Schmitz (European Central Bank (ECB), 2012)
In light of rapidly increasing foreign equity liability positions of emerging market economies, we test for a necessary condition of international risk sharing, namely for systematic patterns between idiosyncratic output fluctuations and financial market developments. Panel analysis of 22 emerging market economies shows strong evidence for pro-cyclicality of capital gains on domestic stock markets both over short and medium term horizons. This implies that domestic output fluctuations can be hedged through cross-border ownership of financial markets.
Keywords: F21; F30; G15; 330; capital gains; Cross-Border Investment; Emerging market economies; financial globalisation; International risk sharing